From housing bust to credit crunch: Evidence from small business loans. (22nd March 2016) - Huang, Haifang; Stephens, Eric
Abstract: This paper provides evidence that the 2007–2009 housing bust in the United States precipitated a "credit crunch" for small businesses. To remove demand‐driven correlations, we rely on within‐city comparisons. We ask whether banks whose mortgage portfolios were more heavily weighted in harder‐hit cities cut back lending to a greater extent in all cities where they make small business loans, relative to other banks in those cities. The evidence is consistent with a credit crunch. Large banks reacted with heavier cuts, but consistent evidence is also found among smaller banks. Quantitatively, the detected contribution to the overall decline in lending from the crunch appears modest. Résumé: Effondrement du marché immobilier et contraction du crédit: résultats dérivés des prêts aux petites entreprises . Ce texte montre que l'effondrement du marché immobilier aux États‐Unis en 2007‐2009 a précipité une contraction du crédit pour les petites entreprises. Pour éliminer les corrélations en provenance de la demande, on s'en tient des comparaisons à l'intérieur de mêmes villes. On se demande si les banques dont les portefeuilles d'hypothèques étaient davantage plombés par les villes les plus durement touchées ont sabré dans les prêts aux petites entreprises dans toutes les villes dans lesquelles elles opéraient, que les autres banques qui opéraient dans ces villes. Les résultats sont cohérents avec l'idée d'une contraction du crédit. Les grandes banques ont réagi avec des contractions plus fortes, mais les petites banques ont réagi aussi dans le même sens. Quantitativement, la contribution au déclin total des prêts dans la contraction du crédit paraît modeste.